Assessment of the performance of three ultrafiltration membranes for fractionation of ovine second cheese whey. (September 2015) - Macedo, Antónia; Duarte, Elizabeth; Fragoso, Rita
Abstract: Second cheese whey (SCW) is a whey by-product resulting from the production of ovine whey cheeses, by thermal aggregation of proteins. It constitutes a natural source of valuable compounds, such as proteins, small peptides, oligosaccharides, lactose and minerals. In this work, ultrafiltration was used for fractionation of second cheese whey. Three commercial membranes with similar cut-off (10 kDa), made from different hydrophilic materials: RC70PP (cellulose regenerated acetate), ETNA10PP (composite fluoro polymer) and UFX10pHt (polysulphone permanently hydrophilic) were tested. The performance of the three membranes was studied in terms of permeate fluxes, reversible and irreversible fouling resistances, water recovery fluxes and rejection factors. Membrane RC70PP showed better performance, because it had the highest permeate fluxes, the lowest irreversible fouling, with good selectivity (compared with that of membrane ETNA10PP) and water recovery fluxes of about 100%. The higher hydrophilicity of membrane RC70PP seems to justify these results.